How do biodiesel blend mandate (B5) effect Malaysian palm oil market model? - Applanaidu, Shri Dewi; Md Ali, Anizah; Alias, Mohammad (IDOSI Publications, 2014)
Over the last ten years biofuels production has increased dramatically.The increment in production has been driven by governmental interventions.In the United States, strong financial incentives are guaranteed for biofuel manufacturers while in the European Union, biofuel consumption is mostly driven by blending mandates.In the case of Malaysia, the blend of palm oil based biodiesel into diesel in all government vehicles was implemented in February 2009 and it is expected to be implemented nationwide in the nearest time.This paper seeks to examine the effect of biodiesel blend mandate (B5) on the Malaysian palm oil market.A system of equations of eight structural equations and four identities is estimated by two-stage least squares method using annual data for the period 1976 - 2011.The results suggest that biodiesel blend mandate (B5) significantly affects domestic demand.Hence, our results support neutrality of palm oil commodity markets in Malaysia to direct effects of biodiesel blend mandate. Then, the elasticity of Malaysian palm oil domestic demand with respect to biodiesel blend mandate is obtained.Results suggest that biodiesel blend mandate has a positive effect on the Malaysian palm oil domestic demand.Thus, the implementation of blend mandate is important in explaining Malaysian palm oil domestic demand.This finding also could be important for marketing strategies such as differentiation of product from food base for fuel use.In terms of government policy, the blend mandate (B5) should be implemented by the Malaysian government if the objective is to boost domestic consumption.